Lobaplatin inhibits prostate cancer progression in part by impairing AR and ERG signal. (30th May 2018) - Chen, Lei; Cao, Hongwen; Yu, Chao; Feng, Yigeng
Abstract: Lobaplatin is the third‐generation platinum drug that has been shown promising antitumor activity in preclinical studies and clinical trials for multiple human cancers except prostate cancer. In this study, we investigated the role of lobaplatin on prostate cancer progression and the underlying molecular mechanism. We treated a variety of prostate cancer cell lines with different doses of lobaplatin and examined cell cycle progression, cell apoptosis, cell proliferation, and cell migration. Moreover, we also assessed the in‐vivo antitumor activity of lobaplatin using xenograft mouse model. Importantly, we further dissected the underlying molecular mechanism by examining the expression of AR and ERG, as well as their downstream targets. We found that lobaplatin arrested cell cycle progression in G2/M phase and trigged cell apoptosis. Lobaplatin also dramatically inhibited cell proliferation and migration in vitro. Consistently, lobaplatin significantly suppressed tumor growth in xenograft mouse model. Mechanistically, the expression of AR and ERG, as well as their downstream targets, was markedly decreased upon treatment with lobaplatin in prostate cancer cells. Altogether, our results suggest that lobaplatin displayed favorable antitumor activity on prostate cancer both in vitro and in vivo, providing molecular basis and rational for using lobaplatin to combat human prostate cancer.